Spillovers from China onto Sub-Saharan Africa : Insights from the Flexible System of Global Models (FSGM) - Anderson, Derek (IMF Working Papers; Working Paper ;, 2015)
What is the impact of economic spillovers from China on sub-Saharan Africa (SSA)? This is an increasingly important question because of China's growing economic role as a partner of SSA countriesfor both trade and the buildup of infrastructure in the region. The impact of spillovers from China has been an open question because of the challenge to use an internally consistent framework with solid economic foundations that accounts for both the direct impact China may have on individual countries in SSA through a variety of channels (trade, investment, financial) as well as the impact on the region through the global economy (economic activity and commodity prices). This paper explores those channels of transmission and provides illustrative order of magnitude for the short- and medium-term economic impact by using AFRMOD, a module of the Flexible System of Global Models (FSGM), a multicountry general equilibrium model developed at the IMF. Three alternative scenarios are considered: first, lower potential output in China that is originally misperceived as a temporary cyclical slowdown; second, structural reforms in China that aim to increase potential output; and third, a relocation of low-end manufacturing to sub-Saharan Africa.